Global forest management, carbon sequestration and bioenergy supply under alternative shared socioeconomic pathways. (April 2021) - Daigneault, Adam; Favero, Alice
Highlights: Global forest sector impacts vary widely across the five shared socioeconomic pathways (SSPs). Roundwood prices, timber harvests, and forest carbon sequestration increase across all SSPs. Global forest area changes between 2015 and 2105 range from -970 (SSP3) to +840 (SSP1) million hectares. Estimates are sensitive to assumptions about wood-based bioenergy demand. Abstract: Socio-economic and technological drivers will strongly shape the future of the global timber market, forest area and climate change mitigation potential, however impacts could vary widely across several plausible futures. This paper illustrates how Shared Socioeconomic Pathways (SSPs) can be applied to forest sector modelling using a method that translates qualitative narratives into quantitative parameters and then applying them to a dynamic global timber model framework. Results indicate wide variations in estimates for key forest sector outputs across the five SSPs with largest impacts on wood prices and forest area. The price estimates have a strong correlation with the other results, as higher timber prices incentivize land to remain in forests, more intensive management, and greater roundwood harvests. Competing influences such as population growth, economic development, land use policy, and technological change could result in wide changes in forest area, ranging from −970 Mha to +840 Mha between now and 2105. Despite large variations across the SSPs, global forests are likely to remain a net carbon sink, with the average annual global forest carbon sequestration ranging from 1.8 GtCO2e/yr to 6.9 GtCO2e/yr. The results of our study, including sensitivity analysis, support developing policies directed towards expanding forest cover or curbing deforestation in an effort to increase forest carbon by focusing on effective ways to enhance technological change, promote sustainable economic development, improve land use protection, and shift consumer preferences towards longer-lasting wood products, which will all raise the relative value of forests across the globe.